Une île impossible : l’utopie néo-humaine comme diagnostic du lien social contemporain chez Michel Houellebecq - Alice Bottarelli; Colin Pahlisch (ReS Futurae)
In The Possibility of an Island, Houellebecq convokes codes of writing peculiar to science fiction, in order not simply to propel the reader into a purely imaginary and uprooted world, but also to reflect upon certain questions related to present-time and social reality. The science fiction intertext which he calls upon allows him to echo numerous reflections from past and present authors, who before him used the genre of utopia to think about the “public sphere”, its codes of communication, and the notion of social links. Indeed, the genre has very soon served as a tool to question the quality of people’s social life, and the utopian novel has been a space where authors could offer a diagnosis of “social pathologies” (the term is borrowed from Axel Honneth). Yet Houellebecq also plays with science fiction codes by conspicuously showing them as literary effects, which renders a first-degree reading of the text very ambiguous. It is therefore interesting to examine precisely how he involves these methods of writing in his texts, and for which purpose. Without suggesting any final resolution or outcome, as a thesis novel or a politically committed novel might do, his work highlights various problems linked to modes of relation – relation to time, to the self and to the other. Evolving (or rather stagnating) in a perpetual present, centred on a self which has lost all its solidity, detached from the possibility of having direct relationships with other individuals, the clones are becoming the victims of a form of virtualisation of all social links, a phenomenon described and criticised by Houellebecq as already being part of our present.